Empowerment of Sector Outside Agriculture as One of The World Started Land Resources - Dewa Nyoman Sadguna; Ni Komang Alit Astiari; Ni Putu Anom Sulistiawati; Made Suarta (SEAS (Sustainable Environment Agricultural Science), 2017)
The porpuse of this research is to know how big result of work outside agriculture sector can give guarantee of survival of farmer's household in Cemagi Village, Mengwi Sub-district, Badung Regency, Bali Province. The method used in the research is purporsive sampling method is a way of determining the location deliberately on the basis of consideration. The village is one of the villages that most of the farmers use their spare time to do work outside the agricultural sector, and no similar research has ever been done. The data used in this research are primary data and secondary data. Data collection methods used were interviews and questionnaires. The data is analyzed by dividing household income from outside agriculture sector with the total income of farmer household and then suppressed. Data the results of the interview if the respondents data interviewed showed that the work outside the agricultural sector utilized by most of the villagers of Cemagi who worked as farmers to improve the welfare of farm households doing work outside the agricultural sector on the sidelines of time to spare. The results of the analysis of respondents if the data data show work outside the agricultural sector that is utilized by most of the people of Cemagi Village who work as farmers to improve the welfare of household farmers as much; 24.05%, doing work outside the agricultural sector on the sidelines of leisure time. The work done include: as a builder of the house accounted for 31.35%, as sand transport workers as much as 24.75%, and the rest there as a truck driver. As hotel employee and villa 28.80 % and as 16.52% of the rest there are as entrepreneurs and others. Looking at the considerable contribution of the carpentry sector, the work can still be undertaken by the farmers of respondents as long as no other work is considered better in helping to increase the income of farm households. Keywords: agricultural sector, revenue, sector outside agriculture